IMPLEMENTASI PRINSIP-PRINSIP GOOD GOVERNANCE PADA PEMERINTAHAN DESA KEREKEH - Roos Nana Sucihati; Vivin Fitryani; K Khairuddin; S Suprianto (Samalewa: Jurnal Riset & Kajian Manajemen, 2021)
This research aims to find out the extent of the application of good governance principles to the government in Kerekeh Village. This type of research is descriptive research with a qualitative approach. This method is used to see whether the good governance principles has been properly implemented in Kerekeh Village, while qualitative data comes form interviews regarding the object of the research. The interviewee in the study are the head of village, the village secretary, the chairman of BPD and the 8 community representatives from each hamlet as wellas the secretary of the Community and Village Empowerment Office of Sumbawa as additional informant. Data analysis is conducted with Miles and Huberman qualitative data analysis techniques that include data collection, data reduction, data presentation and conclusion/verification. Data validity testing is conducted by discussing with academic advisor and colleague. The findings of this study show that the application of nine basic principles of good governance in Kerekeh Village area is not optimal. The not optimal implementation the good governance principles are due to the area of the village is quite wide and the distance between villages (hamlets) is far enough that it becomes an obstacle in establishing a relationship between the government and the community. Therefore, synergy between the government and the community is necessary in order to realize a good village governance order in accordance with the good governance principles